Europese fondsen in Brussel: van principes tot praktijk - Gaëlle Hubert (Brussels Studies)
The present article focuses on the way in which the Brussels Region uses European Structural Funds – in particular the European Regional Development Fund (ERDF) – in view of carrying out several economic and social projects in its territory. It attempts to analyse the evolution of ERDF programmes in Brussels from 2000 to 2013 and takes a critical look at the so-called “regional policy” in this area. The latter is having a hard time getting through the institutional barriers and is characterised by strong inequalities between stakeholders – during the elaboration of programmes as well as in the implementation of projects – despite approaches based on partnership and integration which characterise the European Funds. By taking the European Funds in Brussels as an example, this article examines the logic of “concrete public action”, between strategic policy and incremental process, and between formal procedures and the concrete practices of stakeholders.